ทฤษฎีทางเศรษฐศาสตร์ว่าด้วยผลกระทบภายนอกเชิงลบและการขนส่งทางทะเล: The Economic Theory of Negative Externality and Maritime Transportation - เสนารักษ์, เฉลิมพงษ์ (Journal of Applied Economics and Management Strategy, 2018)
บทความนี้มีวัตถุประสงค์ที่จะอธิบายถึงหลักการทางเศรษฐศาสตร์ว่าด้วยเรื่องผลกระทบภายนอกเชิงลบจากการขนส่งสินค้าทางทะเลระหว่างประเทศ และอธิบายถึงหลักการของอนุสัญญาระหว่างประเทศว่าด้วยการป้องกันมลพิษจากเรือ (MARPOL 73/78) ซึ่งใช้เป็นแนวทางในการแก้ไขปัญหาผลกระทบภายนอกเชิงลบจากการขนส่งทางทะเลในปัจจุบัน และเนื่องจากอนุสัญญาดังกล่าวมีผลบังคับใช้กับประเทศไทย ด้วยเหตุนี้ผู้เขียนจึงได้อธิบายถึงสถานการณ์ปัจจุบัน และแนวทางเบื้องต้นในการจัดการปัญหาจากผลกระทบภายนอกเชิงลบจากการขนส่งทางทะเลของประเทศไทย ทั้งนี้การขนส่งทางทะเลระหว่างประเทศเป็นกิจกรรมที่ก่อให้เกิดมลพิษทางทะเล ซึ่งส่งผลกระทบภายนอกเชิงลบต่อสิ่งแวดล้อมภายนอก ได้แก่ สิ่งมีชีวิตทั้งพืชและสัตว์ คุณภาพชีวิตของคนในสังคม ตลอดจนการพัฒนาเศรษฐกิจของประเทศ ซึ่งในเวทีการค้าโลกสนับสนุนให้ทุกประเทศที่มีการขนส่งทางทะเลปฏิบัติตามบทบัญญัติของอนุสัญญาระหว่างประเทศว่าด้วยการป้องกันมลพิษจากเรือเป็นอย่างมาก โดยเฉพาะอย่างยิ่งรัฐภาคีของอนุสัญญา และประเทศคู่ค้าของรัฐภาคี ในปัจจุบันประเทศไทยได้เข้าเป็นภาคีของอนุสัญญาดังกล่าวเป็นที่เรียบร้อยแล้ว และกำลังพัฒนากฎหมายภายในประเทศให้สอดคล้องกับหลักการของอนุสัญญาอย่างต่อเนื่อง ทั้งนี้เพื่อแก้ไขปัญหาความเสื่อมโทรมของคุณภาพน้ำในทะเลของประเทศไทย โดยเฉพาะอย่างยิ่งในบริเวณอ่าวไทยตอนใน และอ่าวไทยฝั่งตะวันออก This article aims to explain on the economic theory of the negative externality from the perspective of international sea freight, and to demonstrate in the regulations of the International Convention for the Prevention of Pollution from Ships (MARPOL 73/78), which are currently utilized to remedy the negative externalities aggravated from maritime transportation. Moreover, thanks to the present enforcement of convention’s measures on Thailand, the author; therefore, depicts on the current situation as well as the fundamental guidance for the control of negative externalities exacerbated from sea transportation of Thailand. All in all, global maritime transportation is classified as marine pollution-generating activity aggravating negative impacts on the surrounding environment such as living creatures-plants and animals, the living quality of people in society, together with the development of national economy. In the international arena, every country, which provides sea transportation service, is encouraged to comply with the adopted regulations of MARPOL convention, especially states parties and their trader countries. At present, Thailand has already accessed to this convention and has gradually developing its own national laws in accordance with the convention’s regulations in order to solve water quality deterioration in maritime zone of Thailand especially the Inner and Eastern gulf of Thailand.